Nonlinear optical phenomena : Compressor of femtosecond laser pulses based on supercritical xenon. (26th July 2018) - Didenko, N V; Konyashchenko, A V; Losev, L L; Pazyuk, V S
Abstract: A time compressor of femtosecond laser pulses is developed using supercritical xenon as an active medium. Laser pulses with a duration of 300-fs and an energy of 8 mJ are compressed to 23 fs with an efficiency of 40%.